Examining the epigenetic transmission of risk for chronic pain associated with paternal post-traumatic stress disorder: a focus on veteran populations - James Freeman; Sabrina Salberg; Melanie Noel; Richelle Mychasiuk (Translational Psychiatry)
Abstract Chronic pain is a public health problem that significantly reduces quality of life. Although the aetiology is often unknown, recent evidence suggests that susceptibility can be transmitted intergenerationally, from parent to child. Post-traumatic stress disorder (PTSD) is a debilitating psychological disorder, often associated with chronic pain, that has high prevalence rates in military personnel and Veterans. Therefore, we aimed to characterise the epigenetic mechanisms by which paternal trauma, such as PTSD, is transmitted across generations to confer risk in the next generation, specifically focusing on Veterans where possible. Numerous overlapping neurological pathways are implicated in both PTSD and chronic pain; many of which are susceptible to epigenetic modification, such as DNA methylation, histone modifications, and RNA regulation. Hence, epigenetic changes related to pain perception, inflammation, and neurotransmission may influence an individual’s predisposition to chronic pain conditions. We also examine the effects of PTSD on parenting behaviours and discuss how these variations could impact the development of chronic pain in children. We highlight the need for further research regarding the interactions between paternal trauma and epigenetic processes to ultimately generate effective prevention and therapeutic strategies for Veterans who have been affected by PTSD and chronic pain.